Depression in cancer patients: Magnitude of problem and factors responsible - Kartick Rastogi; Amrita Rakesh; Subhash Chand Bairwa; Sandeep Bhaskar; Shivani Gupta; Shantanu Sharma; Sandeep Jain (Indian Journal of Medical and Paediatric Oncology)
Context: Cancer patients usually have various psychological complications, depression being the most common among them. Depression poses difficulties in continuing the prescribed treatment within the scheduled time frame, ultimately affecting the outcome. Aims: The aims of this study were to determine the magnitude of depression and various factors associated with it, to initiate the timely intervention. Subjects and Materials: Brief Edinburgh Depression Scale was used to measure depression in 203 cancer patients who received chemotherapy at Department of Radiotherapy, SMS Medical College, Jaipur; in August 2017, were above 18 years of age, and could read, understand, and write. Association of depression with various factors such as age, gender, education and occupation details, income, marital status, history of other comorbid disease, type and site of cancer, presence of metastases, number of chemotherapy cycles going on, and source of cost of therapy, was also computed. Results: Of 203 patients, depression was present in 130 (64%) patients. Statistically significant association of depression was found with both extremes of the age (P = 0.04), paid treatment (P = 0.03), and <4 chemotherapy cycles (P = 0.04). No significant association was seen between depression and gender, occupation, performance status, site of cancer, presence of coexisting disease, and metastases. Conclusions: The magnitude of depression was high (present in 64% of patients) which often gets unnoticed. Depression should routinely be screened among cancer patients receiving chemotherapy and patients found to have depression should be referred to a psychiatrist for timely management.